2023
DOI: 10.3389/fimmu.2023.1307455
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miRNAs in autoimmune skin diseases

Ri Zhang,
Yujia Wei,
Tingmei Wang
et al.

Abstract: Exosomes, bilaterally phospholipid-coated small vesicles, are produced and released by nearly all cells, which comprise diverse biological macromolecules, including proteins, DNA, RNA, and others, that participate in the regulation of their biological functions. An increasing number of studies have revealed that the contents of exosomes, particularly microRNA(miRNA), play a significant role in the pathogenesis of various diseases, including autoimmune skin diseases. MiRNA is a class of single-stranded non-codi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, circulating miRNAs are stable, less susceptible to degradation than RNA, and easily detectable and quantifiable by sensitive methods in different types of body fluids, first and foremost being blood and plasma [ 23 , 79 , 94 , 114 ]. These characteristics make them reliable biomarkers for the diagnosis and discrimination of several autoimmune diseases, including SSc, as demonstrated in several studies so far [ 79 , 107 , 109 , 110 , 112 , 182 , 183 ].…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, circulating miRNAs are stable, less susceptible to degradation than RNA, and easily detectable and quantifiable by sensitive methods in different types of body fluids, first and foremost being blood and plasma [ 23 , 79 , 94 , 114 ]. These characteristics make them reliable biomarkers for the diagnosis and discrimination of several autoimmune diseases, including SSc, as demonstrated in several studies so far [ 79 , 107 , 109 , 110 , 112 , 182 , 183 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…The diagnosis and treatment of ADs, especially of rare diseases such as SSc, are often hampered by challenges due to the complexity of the identification of initial symptoms; the poor knowledge of the disease; and the lack of rapid, accurate, and universally recognized diagnostic markers. Therefore, in recent years, growing interest has been given to the use of miRNAs as potential biomarkers or innovative therapeutic approaches [ 6 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“… 267 Analysis of serum‐derived EV microRNAs also demonstrated that a variety of microRNAs were associated with MS recurrence and activity, 264 , 268 , 269 and can be used to support personalized treatment decisions. Exosomes are also used in the diagnosis and monitoring of immune disorders such as multifocal leukoencephalopathy (PML), 270 Sjögren's syndrome, 271 autoimmune skin diseases, 272 IgA neuropathies, 273 adult myasthenia gravis, 274 and inflammatory bowel disease. 275 , 276 …”
Section: Exosome Biomarkersmentioning
confidence: 99%
“…Consequently, the role of exosomal miRNA in the regulation of cancer progression is substantial, making them promising candidates as diagnostic and therapeutic biomarkers ( Sun et al, 2018 ). Additionally, besides their involvement in tumors, evidence indicates that exosome miRNA is implicated in corneal diseases ( Verma et al, 2023 ; Arora and Verma, 2024 ), complications of diabetes ( Xu et al, 2022 ), and autoimmune skin diseases ( Zhang R. et al, 2023 ). Hence, they possess the potential to serve as biomarkers and therapeutic targets in these conditions.…”
Section: Exosomal Mirnas As Potential Biomarkers For the Treatment Of...mentioning
confidence: 99%